6x-5x=+1

Simple and best practice solution for 6x-5x=+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-5x=+1 equation:


6x-5x=+1

We simplify the equation to the form, which is simple to understand
6x-5x=+1

We move all terms containing x to the left and all other terms to the right.
+6x-5x=+1

We simplify left and right side of the equation.
+1x=+1

We divide both sides of the equation by 1 to get x.
x=1

See similar equations:

| 6w-14-9w=-5 | | 5-3*-1= | | 12y-3y+7=88 | | 8x^2+3x-7=0 | | 22p+11= | | 8(y+3)=2(2y+4) | | 4w^2+5=-21w | | 2(3)-5y=13 | | 7y=20 | | 3(x-2)+4x=8 | | 3x-10-5+6x=12 | | 4(7x-2)-16x= | | 7u=2u^2-4 | | z^2-13z+18=0 | | 5x(x-23)=-37 | | 20=4(d+3) | | (7+2a)+3a= | | 2-5y=13 | | 4(-3)+6(-8)+(-3)(78)-7(-42)= | | 6+x-x^2=0 | | n-12=5n+4 | | .4b+1=-11 | | 5x(x-23)=37 | | p+3p+2P=180 | | 12x^3+58x^2+70x= | | 13+(3xx)=50 | | x-2+x+x+5=40 | | 3w^2-11w=-6 | | 5m+2m-42=14 | | 0.3(3y-12)=6-2(y-1) | | (5u-2)(1+u)=0 | | (2x^2-6x+16x+8x-24x+16)*(x^2+5x-2)=(2x+4)*(x^2+5x-2)*(x+4) |

Equations solver categories